Wheels of Change: Transforming Girls' Lives with Bicycles - Nathan Fiala; Ana Garcia-Hernandez; Kritika Narula; Nishith Prakash (Center for Economic Studies and ifo Institute (CESifo), 2022)
Reducing the gender gap in education is a primary goal for many countries. Some major challenges for many girls include the distance to school, their safety when commuting to school, lack of agency, and deep-rooted cultural norms. In Zambia, we studied the impact of providing a bicycle to a school-going girl who lives more than 3 km from the school. We randomized whether a girl received a bicycle with a small cost to her family to cover replacement parts, a bicycle where these costs are covered by the program, and therefore is zero cost to the family, or a control group. One year after the intervention, we find that the bicycle reduced average commuting time to school by 35%, reduced late arrival by 66%, and decreased absenteeism by 27%. We find continued improvement in girls' attendance and reduction in dropouts two, three, and four years after the intervention. We also find evidence of improved math test scores, girls expressing higher feelings of control over their lives and, for those who received bicycles with a small cost to her family, higher levels of aspirations, self-image, and a desire to delay marriage and pregnancy. Heterogeneity analysis by distance to school shows an inverted U-shape for most of the schooling and empowerment results, suggesting greater impact for girls that live further away from school. These results suggest that empowerment outcomes worked through increased attendance in school.
Keywords: H42; I21; I25; J16; O15; 330; bicycles; commute time; girls' education; female empowerment; safety; Zambia